Analyzing Factors of Turnover Intention at PT. Sumber Alfariya Trijaya Tbk - Nindhita, Yoga; Saputro, Purnomo Herry; Prawani, Dwi (Management Analysis Journal, 2022)
Turnover intention is a problem in many companies today. This study aims to determine the effect of job satisfaction, work stress, compensation, and career development on shop employee turnover intention at PT. Sumber Alfariya Trijaya Tbk. Semarang branch. This study uses quantitative methods, with descriptive and statistical types of analysis. The population in the study was 449 people and 82 respondents were taken. Sampling using a simple random sampling technique, respondents are employees of PT. Sumber Alfariya Trijaya Tbk Semarang. The analytical model used in this study is multiple linear regression. The F test also shows that all the independent variables in this study simultaneously affect the turnover intention of PT. Sumber Alfariya Trijaya Tbk. Semarang and the variable that has the dominant influence is the variable job satisfaction. The practical implications of the results of this study are that PT. Sumber Alfariya Trijaya Tbk. The Semarang branch needs to provide more compensation to employees to reduce the turnover rate. For career development and the level of employee job satisfaction needs to be maintained and it is necessary to reduce the level of work stress of employees.